Seasonal variability of atmospheric nitrogen oxides and non-methane hydrocarbons at the GEOSummit station, Greenland - Kramer, L. J.; Helmig, D.; Burkhart, J. F.; Stohl, A.; Oltmans, S.; Honrath, R. E. (Digital Commons @ Michigan Tech, 2015)
Measurements of atmospheric nitrogen oxides NOx (NOx = NO + NO2), peroxyacetyl nitrate (PAN), NOy, and non-methane hydrocarbons (NMHC) were taken at the Greenland Environmental Observatory at Summit (GEOSummit) station, Greenland (72.34° N, 38.29° W; 3212 m a.s.l.), from July 2008 to July 2010. The data set represents the first year-round concurrent record of these compounds sampled at a high latitude Arctic site. Here, the study focused on the seasonal variability of these important ozone (O3) precursors in the Arctic troposphere and the impact from transported anthropogenic and biomass burning emissions. Our analysis shows that PAN is the dominant NOy species in all seasons at Summit, varying from 42 to 76 %; however, we find that odd NOy species (odd NOy = NOy - PAN - NOx) contribute a large amount to the total NOy speciation. We hypothesize that the source of this odd NOy is most likely alkyl nitrates and nitric acid (HNO3) from transported pollution, and photochemically produced species such as nitrous acid (HONO). FLEXPART retroplume analyses and black carbon (BC) tracers for anthropogenic and biomass burning (BB) emissions were used to identify periods when the site was impacted by polluted air masses. Europe contributed the largest source of anthropogenic emissions during the winter months (November-March) with 56 % of the total anthropogenic BC tracer originating from Europe in 2008-2009 and 69 % in 2009-2010. The polluted plumes resulted in mean enhancements above background levels up to 334, 295, 88, and 1119 pmol mol-1 for NOy, PAN, NOx, and ethane, respectively, over the two winters. Enhancements in O3 precursors during the second winter were typically higher, which may be attributed to the increase in European polluted air masses transported to Summit in 2009-2010 compared to 2008-2009. O3 levels were highly variable within the sampled anthropogenic plumes with mean ΔO3 levels ranging from -6.7 to 7.6 nmol mol-1 during the winter periods. North America was the primary source of biomass burning ...